PENTINGNYA PENDIDIKAN KARAKTER DI SEKOLAH DASAR (SD) DALAM UPAYA PENCEGAHAN BULLYING - Putri Patricia Novelina Purba; Kesya Malika Nurluthvia; Andre Patoman Simatupang; Akhmat Faisal Hidayat (Al-Thifl: Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to provide comprehensive guidance for educators in addressing bullying behaviour and improving the morals and character of primary school students through the implementation of character education. Bullying is a serious problem that often arises in primary school environments and can have a negative impact on students' social, emotional, and academic development. Therefore, continuous preventive and solution-oriented efforts are needed through an early character education approach. The research method used in this study was a literature review, which examined and analysed 16 relevant references from scientific journals, books, and other academic sources. The results of the study show that character education plays a very significant role in shaping empathy, tolerance, responsibility, and mutual respect in students, thereby reducing the occurrence of bullying behaviour at school. Strengthening character values such as honesty, discipline, cooperation, and social awareness has proven to be effective in creating a safe and conducive learning environment. Bullying can be addressed and prevented in an integrated manner through the curriculum, learning activities, and the exemplary behaviour of teachers and educators. Thus, this study is expected to serve as a practical reference for primary schools in designing and implementing effective and sustainable character education programmes to create a positive and bullying-free school climate.